2009
DOI: 10.1038/sj.bjc.6605218
|View full text |Cite|
|
Sign up to set email alerts
|

Uracil-tegafur and tamoxifen vs cyclophosphamide, methotrexate, fluorouracil, and tamoxifen in post-operative adjuvant therapy for stage I, II, or IIIA lymph node-positive breast cancer: a comparative study

Abstract: BACKGROUND: It has been reported that treatment with uracil-tegafur (UFT) has shown significantly better survival and relapse-free survival (RFS) than surgery alone. Therefore, we compared UFT with a combination therapy of cyclophosphamide, methotrexate, and fluorouracil (CMF) in patients who had undergone curative surgery for axillary lymph node-positive breast cancer. METHODS: A total of 377 node-positive patients with stage I, II, or IIIA disease were registered from September 1996 through July 2000 and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…In both studies, relapse-free survival (RFS) and OS at 5 years after surgery were similar in the CMF and UFT groups (Figures 7 and 8). The CUBC trial showed a trend towards better RFS in the UFT group than in the CMF group among women whose tumors were estrogen receptor (ER) and progesterone receptor positive [8] .…”
Section: Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…In both studies, relapse-free survival (RFS) and OS at 5 years after surgery were similar in the CMF and UFT groups (Figures 7 and 8). The CUBC trial showed a trend towards better RFS in the UFT group than in the CMF group among women whose tumors were estrogen receptor (ER) and progesterone receptor positive [8] .…”
Section: Chemotherapymentioning
confidence: 99%
“…In 2009, the results of the National Surgical Adjuvant Study for Breast Cancer 01 Trial (NSAS-BC01) [7] and the Comparative Trial of UFT + Tamoxifen with CMF + Tamoxifen in Adjuvant Therapy for Breast Cancer (CUBC) [8] -two recent Japanese clinical trials designed to establish whether intravenous or oral treatment was superior for postoperative adjuvant chemotherapy -were reported. The NSAS-BC01 trial compared CMF with UFT in high-risk patients with axillary node negative breast cancer.…”
Section: Chemotherapymentioning
confidence: 99%
“…Six trials of adjuvant chemotherapy (21,22,(44)(45)(46)(47), 1 trial of neoadjuvant chemotherapy (48), and 2 trials of radiotherapy (49,50) were published on early breast cancer (Table 3). Active controls in the adjuvant and neoadjuvant chemotherapy trials included CMF, doxorubicin þ cyclophosphamide, or doxorubicin þ cyclophosphamide þ docetaxel.…”
Section: Review In Selected Cancersmentioning
confidence: 99%
“…The Comparative Trial with UFT ϩ TAM and CMF ϩ TAM in Adjuvant Therapy for Breast Cancer [9,10] was conducted during the same period as the N-SAS-BC 01 study to verify that UFT is noninferior to CMF in patients who had stage I to IIIa breast cancer with one to nine axillary node metastases. That study compared six cycles of CMF plus 2 years of TAM with UFT plus TAM for 2 years.…”
Section: Usefulness Compared With Cmfmentioning
confidence: 99%